Emergency care and transportation of the sick and injured : case studies - McNeill, Beth Ann (Jone & Barlett Learning, 2013)
This manual is the ideal student supplement, in support of case-based learning, to Emergency Care and Transportation of the Sick and Injured, Tenth Edition.